A study on students' satisfaction over academic services provided by Jerantut community college / Che Rafidah Che Nali - Che Nali, Che Rafidah (2013)
Students of any private or public higher learning institutions can be regarded as customers to these organizations. Thus, it is very important to take care of their satisfaction in ensuring the best service and a quality education are delivered to them. Student satisfaction can improve the image of that education institution as well as attracting more students to enroll at that education institution. Community College is one of the public higher learning institutions which responsible in providing good education to youth in helping them developing a better life in the future. This study was carried out in Community College in Pahang which only offering certificate courses for their students. The Community College involved in this study is Jerantut Community College. Other than that, this study was focused on students' satisfaction over academic services quality provided by the Community College. The students' satisfaction has been measured based on SERVQUAL five dimensions developed by Parasuraman et al. The five dimensions are tangible, reliability, responsiveness, assurance, and empathy. The sampling technique used in getting the sample size was stratified random sampling. All the findings were reported in forms of texts, tables, as well as figures . Overall, it can be concluded that students of Jerantut Community College had high satisfaction over the academic services provided. Last but not least, it was recommended for Jerantut Community College to improve the tangibles quality in providing academic services for its students.